Management of Central Serous Chorioretinopathy (CSC) with Focal Laser Photocoagulation: Poster Presentation - Case Report - Resident - Aziztama, Rezandi; Amin, Ramzi; Ansyori, AK (Majalah Oftalmologi Indonesia, 2023)
Introduction : Central Serous Chorioretinopathy (CSC) is an idiopathic retinal disease, characterized by focal leakage from the choroidal vessels due to RPE changes resulted in serous detachment of the neurosensory retina. CSC is suspected to be a multifactorial disease. Treatment of CSC is indicated for cases with SRF persisting for more than 4 months, decreased visual acuity, history of recurrence or history of previous CSC in other side with poor visual outcome. Case Illustration : A 41-year-old man complained sudden blurry vision on left eye since 3 months ago, accompanied by decreased ability to see in the middle field. In the left eye there was decrease fovea reflex. Fundus Fluorescein Angiography showed Central Serous Chorioretinopathy (CSC). Laser Focal Photocoagulation was performed for a patient in this case. Discussion : Conclusion : Patient was treated with Laser Focal Photocoagulation and pharmacological acetazolamide with the aim of closing the leak in the RPE and increasing SRF absorption.